Screendance Bárbara and its Poetics of ‘BBC’ Dialogues, or Between Body, Beliefs and the City - Tavares, Carlos Gonçalves; Pedreira Vieira, Alba; dos Santos Mendes da Silva , Bruno Miguel (Revista Brasileira de Estudos da Presença, 2023)
The objective is to reflect on how the work Bárbara creates artistic poetics from the dialogue between urban space and screendance, problematizing deeply rooted beliefs from contemporary art and tensioning others, different ones, from digital culture. Principles of practice are adopted as research to discuss the interfaces between dance, audiovisual technology and modern architecture in Cataguases, Minas Gerais. Recording and editing strategies are highlighted in the creative process of the videodance Bárbara, and the state of trance, of estrangement that happened both to the character, when she dared to dance in a sacred space of the city, and to the researcher who dared to venture, in a wandering way, through the hybrid paths of contemporary art that dialogue dance and audiovisual.